Financial configurations and interactions in a transfor-mation process of a global economy - PĂUN, Roxana-Daniela (Annals of Spiru Haret University. Economic Series, 2010)
This article aims to present the summary of issues related to Economic and Monetary Union (EMU) in the context of EU enlargement, analyzing legal rules and practical problems appeared. EMU Stability and Growth Pact is a challenge for Member States in circumstances where exactly the European Union Member States who have campaigned for the budgetary discipline required more relaxed conditions on the provisions of the Pact. Convergence criteria laid down in the Maastricht Treaty (TEU) began to be increasingly difficult to be respected by Member States, therefore it was decided to greater flexibility of restraining and Growth Pact.